From genes to ecosystems: a synthesis of amphibian biodiversity research in Brazil - Haddad, Celio F. B. [UNESP]; Lopes, Carla M. [UNESP]; Becker, C. Guilherme; Silva, Fernando R. da; Lyra, Mariana L. [UNESP] (Revista Biota Neotropica, 2022)
Here, we summarize examples of significant advances in amphibian research supported by the Sao Paulo Research Foundation (FAPESP), focusing on recent discoveries in the fields of community ecology, habitat change, infection diseases, and multipurpose DNA sequencing. We demonstrated that FAPESP has been fundamental not only by directly funding research projects and scholarships, but also through its science training policy, fostering international collaborations with world-class research institutions, improving and consolidating new lines of research that often depended on a synergetic combination of different knowledge and complex tools. We emphasized that future studies will continue to focus on basic questions, such as description of new species, as well as taxonomic and systematic corrections. Furthermore, we also expect that there will be a strong integration among different disciplines using novel bioinformatics tools and modeling approaches, such as machine learning. These new approaches will be critical to further develop our understanding of foundational questions of amphibian life-history trait variation, disease transmission, community assembly, biogeography, and population forecasts under different global change scenarios such as agricultural expansion, agrochemical use, habitat loss, and climate change.
Keywords: Anura; community ecology; Habitat change; DNA sequencing; Chytridiomycosis; FAPESP; Financial support